Serendipity and strategy in rapid innovation. Issue 1 (December 2017) - Fink, T.; Reeves, M.; Palma, R.; Farr, R.
Abstract Innovation is to organizations what evolution is to organisms: it is how organizations adapt to environmental change and improve. Yet despite advances in our understanding of evolution, what drives innovation remains elusive. On the one hand, organizations invest heavily in systematic strategies to accelerate innovation. On the other, historical analysis and individual experience suggest that serendipity plays a significant role. To unify these perspectives, we analysed the mathematics of innovation as a search for designs across a universe of component building blocks. We tested our insights using data from language, gastronomy and technology. By measuring the number of makeable designs as we acquire components, we observed that the relative usefulness of different components can cross over time. When these crossovers are unanticipated, they appear to be the result of serendipity. But when we can predict crossovers in advance, they offer opportunities to strategically increase the growth of the product space. Organizations can take different approaches to innovation: they can either follow a strategic process or a serendipitous perspective. Here Fink et al. develop a statistical model to analyse how components combine to obtain a product and thus explain the mechanism behind the two approaches.